Towards Sustainable Construction: Evaluating Thermal Conductivity in Advanced Foam Concrete Mixtures - Alireza Mohtadi; Mohammad Ghomeishi; Ali Dehghanbanadaki (Buildings)
Traditional concrete structures are frequently linked to poor energy efficiency and substantial heat loss, which pose significant environmental issues. To enhance thermal insulation and reduce heat loss, the use of precast insulated walls is suggested. This research introduces a new energy-efficient precast concrete panel (PCP). We explored various material combinations, including air bubbles, nano microsilica compound (NMC), nano microsilica powder (NMP), and latex, to determine the most effective formulation. A total of 99 tests were performed to assess the compressive strength of the samples, with 28 tests selected for thermal conductivity evaluations at temperatures of 300 °C and 400 °C based on satisfactory compressive strength results. The results indicated that the optimal mix of 4% air bubbles and 13% NMC achieved the lowest thermal conductivities of 1.31 W/m·K and 1.20 W/m·K at 300 °C and 400 °C, respectively, showing improvement ratios of 7% and 15.5% compared to the baseline tests. Additionally, the tests that included latex did not meet the thermal conductivity standards. The optimal combinations identified in this research can be effectively utilized in PCPs, resulting in significant energy savings. It is expected that stakeholders in the green building sector will recognize these proposed PCPs as a practical energy-efficient solution to advance sustainable and environmentally friendly construction practices.